PENERAPAN NETWORK PLANNING PADA PROYEK PEMBANGUNAN PERUMAHAN MUTIARA RESIDENCE DI DESA PENGAMBENGAN KABUPATEN JEMBRANA - Wardhani, Rini Wijaya Kusuma; Mandala, Kastawan (E-Jurnal Manajemen; Vol 7 No 12 (2018)DO - 10.24843/EJMUNUD.2018.v07.i12.p13, 2018)
ABSTRACT The increasing number of construction companies in Indonesia poses a challenge for companies to improve the effectiveness and efficiency of resource management in order to excel among competitors. The purpose of this study is to determine whether the implementation of Network Planning can improve efficiency and effectiveness in the allocation of time and cost on the construction project. The research method is a case study to address the problem at Putra Dewata PT Karya Tama concerning network planning of Mutiara Residence Housing project. Data analysis technique used is Critical Path Method. The results show that the project completion time is 142.5 days, 14.5 days faster than the calculation result by the company with Gantt Chart method. This will provide benefits in terms of cost of completion of the project, where cost efficiencies that can be gained is Rp. 20,807,500.   Keywords : network planning, critical path method, critical path.